Japan Fracture Observational Study (JFOS): patient characteristics and interim data on the use of daily teriparatide in Japanese patients with osteoporosis. (2nd September 2015) - Soen, Satoshi; Fujiwara, Saeko; Takayanagi, Ryoichi; Sato, Masayo; Tsujimoto, Mika; Yamamoto, Takanori; Enomoto, Hiroyuki; Krege, John H.
Abstract: Objectives: This report from the Japan Fracture Observational Study (JFOS) describes the design of the study, baseline characteristics of the patients, and interim results. Research design and methods: This is an interim analysis from an ongoing observational study of male and female patients with osteoporosis initiating daily teriparatide treatment observed at baseline, 3, 6 and 12 months. There was no control group. Baseline data were collected on demographic characteristics, medical and osteoporosis history, prior use of medications and health-related quality of life (HRQoL). This interim analysis includes preliminary information concerning incidence of clinical fractures, bone mineral density (BMD), procollagen type 1 aminoterminal propeptide (P1NP), back pain, HRQoL, and adverse events. Results: Baseline observations were completed for 1810 patients; 90.1% were female. Compared with osteoporotic patients treated with teriparatide in other observational studies, those in JFOS were older but had fewer osteoporosis risk factors. The incidence of clinical fractures was 2.9% at 6 months and 3.7% at 12 months. At 12 months, mean BMD was 8.9% higher at the lumbar spine and 0.8% higher at the total hip compared to baseline. At 6 months, the median serum concentration of P1NP was 187.7% higher than at baseline. At 12 months, back pain scores assessed by visual analog scale (VAS) were lower and HRQoL scores were higher than at baseline. No new safety signals were observed. Conclusions: This is the first report from an observational study of daily teriparatide in Japanese osteoporotic patients at high risk of fractures. Patients in JFOS were older but had fewer osteoporosis risk factors than those treated with teriparatide in other observational studies. The interim analysis suggests that the clinical profile of teriparatide in the real world is similar to that observed in clinical trials and observational studies conducted in Europe and the United States.